A mini-review on decorating, templating of commercial and electrospinning of new porous carbon electrodes for vanadium redox flow batteries. (7th May 2021) - Schnucklake, Maike; Cheng, Ming; Maleki, Mahboubeh; Roth, Christina
Abstract: Carbon-based materials have become indispensable in the field of electrochemical applications, especially for energy storage or conversion purposes. A large diversity of materials has been proposed and investigated in the last years. In this mini-review, we present recent advances in the design of carbon-based materials for application in vanadium redox flow batteries. As main part, different modification and fabrication methods for carbon-based electrodes are described. The decoration of carbon felts and graphite felts with metals or metal compounds to enhance mostly the electrocatalysis of the negative side is illustrated with examples. Furthermore, various options of synthesizing porous C–C composites are discussed, with specific emphasis on graphene-based composites as well as nitrogen doped composites and biomass-derived carbons. Apart from that the method of electrospinning is also examined in detail, a method which not only allows the production of nanofibrous high surface area electrodes, but also allows adaptation of fiber thickness and architecture. In this review the significant strengths of each method are pointed out, but also particular weaknesses are discussed with respect to the later battery performance. Finally, an outlook is given pointing to the remaining challenges that need to be overcome in the future.